Dinamika Sosial Masyarakat Multikultural dalam Relasi Agama di Desa Rama Agung, Bengkulu Utara - Rafiyansyah, Adji; Afrita, Desy; Fadlurrohim, Ishak (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study analyzes the dynamics of a multicultural society in interfaith relations in Rama Agung Village, North Bengkulu Regency. A descriptive qualitative case study approach was employed through in-depth interviews, participatory observation, and documentation involving 20 informants representing Islam, Christianity, and Hinduism. The findings reveal that social interactions occur in four main domains socio-cultural, political, economic, and religious which collectively strengthen solidarity and social cohesion. Social changes are reflected in the increasing openness of attitudes, the transformation of religious leaders’ roles into interfaith mediators, the emergence of more democratic communication patterns, and the creation of new collective cultural values. Meanwhile, social adaptation is manifested through interfaith economic cooperation, participation in cultural and religious rituals, and the establishment of inclusive local political institutions. These three dynamics interaction, change, and adaptation demonstrate that multiculturalism serves not merely as a characteristic of diversity but as a foundation for social harmony and resilience at the local level.